Codigestion of solid wastes: A review of its uses and perspectives including modeling - Mata-Alvarez, Joan; Dosta, Joan; Macé, Sandra; Astals, Sergi (Critical reviews in biotechnology, 2011)
The last two years have witnessed a dramatic increase in the number of papers published on the subject of codigestion, highlighting the relevance of this topic within anaerobic digestion research. Consequently, it seems appropriate to undertake a review of codigestion practices starting from the late 1970s, when the first papers related to this concept were published, and continuing to the present day, demonstrating the exponential growth in the interest shown in this approach in recent years. Following a general analysis of the situation, state-of-the-art codigestion is described, focusing on the two most important areas as regards publication: codigestion involving sewage sludge and the organic fraction of municipal solid waste (including a review of the secondary advantages for wastewater treatment plant related to biological nutrient removal), and codigestion in the agricultural sector, that is, including agricultural - farm wastes, and energy crops. Within these areas, a large number of oversized digesters appear which can be used to codigest other substrates, resulting in economic and environmental advantages. Although the situation may be changing, there is still a need for good examples on an industrial scale, particularly with regard to wastewater treatment plants, in order to extend this beneficial practice. In the last section, a detailed analysis of papers addressing the important aspect of modelisation is included. This analysis includes the first codigestion models to be developed as well as recent applications of the standardised anaerobic digestion model ADM1 to codigestion. (This review includes studies ranging from laboratory to industrial scale.)